Giant Rabi Splitting and Polariton Photoluminescence in an all Solution-Deposited Dielectric Microcavity - Qureshi, Hassan A.; Papachatzakis, Michael A.; Abdelmagid, Ahmed Gaber; Salomäki, Mikko; Mäkilä, Ermei; Tuomi, Oskar; Siltanen, Olli; Daskalakis, Konstantinos S. (WILEY-V C H VERLAG GMBH, 2025)
Planar microcavity polaritons have recently emerged as a promising technology for improving several performance characteristics of organic light-emitting diodes, photodiodes, and photovoltaics. To form polaritons and achieve enhanced performance, traditional microcavities with high reflectivity mirrors are fabricated by energy-intensive physical vapor deposition methods, which restrict their use in applications requiring flexibility and low cost. Here, for the first time, a dielectric all-solution-processed polariton microcavity consisting of Rhodamine 6G films in a poly(vinyl alcohol) matrix is demonstrated, exhibiting more than 400 meV Rabi-splitting and photoluminescence with uniform dispersion along the lower polariton mode. The fully automated deposition and annealing fabrication protocol played a key role in preventing interlayer mixing and producing high optical-quality polariton microcavities, enabling to observe enhanced scattering of reservoir excitons to the lower polariton and to explore the effects of strong coupling on bimolecular interactions. Notably, it is found that polariton microcavities exhibit a more than tenfold increase in the critical excitation density for bimolecular annihilation compared to bare Rhodamine 6G films. This enhancement can only be partially attributed to the sub-threefold measured reduction in radiative lifetime, highlighting the critical role of strong coupling in the influence of molecular dynamics.